Weakly Compact Uniform Attractor for the Nonautonomous Long-Short Wave Equations - Hongyong Cui; Jie Xin; Anran Li (Abstract and Applied Analysis)
Solutions and weakly compact uniform attractor for the nonautonomous long-short wave equations with translation compact forces were studied in a bounded domain. We first established the existence and the uniqueness of the solution to the system by using Galerkin method and then obtained the uniform absorbing set and the weakly compact uniform attractor of the problem by applying techniques of constructing skew product flow in the extended phase space.